Effect of curcumin and three analogues on pre-osteoblast cells’ viability, differentiation, and gene expression - Ana Flor Sá; Ivana Márcia Alves Diniz; Renata Barbosa de Oliveira; Marina Gonçalves Diniz; Maria Esperanza Cortés; Letícia Lopes de Souza; Carlos Delfin Chávez Olórtegui; Frederico Santos Lages (Brazilian Oral Research)
Abstract Curcumin, found in turmeric rhizomes (Curcuma longa L.), has been widely studied for its potential health benefits, including anti-inflammatory, antioxidant, and wound-healing properties. However, due to its low bioavailability and unfavorable pharmacokinetics, analogous compounds have been developed to obtain better biopharmaceutical characteristics and enhanced biological effects. In this study, we evaluated the activity of curcumin and three of its synthetic analogues (DMAD, DMAM, and RI75) on the viability and differentiation of a pre-osteoblastic cell line (MC3T3-E1). We also assessed the expression of key genes involved in tissue regeneration: vascular endothelial growth factor (vegf), stromal-derived growth factor 1 (SDF-1/CXCL12), and runt-related transcription factor 2 (runx2). The cells were treated with curcumin and the three analogues at concentrations of 10, 30, or 50 μM. All tested analogues and curcumin exhibited moderate to no cell toxicity compared to the cells treated under standard conditions across all concentrations after 24, 48, and 72 hours. Only the RI75 analogue showed upregulation of SDF-1, a crucial factor in tissue regeneration. Compared to curcumin, the DMAM and RI75 analogues also upregulated runx2 and vegf, both associated with osteodifferentiation. The RI75 analogue demonstrated greater mineralization than curcumin, and both promoted more nodule formation than the untreated control. Our data suggest that the curcumin analogue RI75 at 50 μM presents similar toxicity but enhanced biological activity compared to natural curcumin, making it a promising substance for material biomodifications.